2004
DOI: 10.12693/aphyspola.106.141
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Crystal Fibers

Abstract: Photonic crystal fibers are a new class of optical fibers. Their artificial crystal-like microstructure results in a number of unusual properties. They can guide light not only through a well-known total internal reflection mechanism but using also photonic bandgap effect. In this paper different properties possible to obtain in photonic crystal fibers are reviewed. Fabrication and modeling methods are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 49 publications
0
69
0
1
Order By: Relevance
“…For a start, the double line defect core cane can be obtained by an extrusion method [36] and a mechanical drilling method [37]. Next, our proposed fiber design can be reliably fabricated by two-step stack-anddraw procedure due to all circular air holes and conventional lattice structure with core cane [38][39][40][41]. For the other method, Bisen et al reported a sol-gel method [42,43] for microand nano-structure fabrication in 2005.…”
Section: Optimization Of Structure Parameters For the Double Linmentioning
confidence: 99%
“…For a start, the double line defect core cane can be obtained by an extrusion method [36] and a mechanical drilling method [37]. Next, our proposed fiber design can be reliably fabricated by two-step stack-anddraw procedure due to all circular air holes and conventional lattice structure with core cane [38][39][40][41]. For the other method, Bisen et al reported a sol-gel method [42,43] for microand nano-structure fabrication in 2005.…”
Section: Optimization Of Structure Parameters For the Double Linmentioning
confidence: 99%
“…The emergence of Photonic Crystal Fiber (PCF) was a breakthrough in the fiber optic technology. Since the invention of PCF using 2D photonic crystal, in 1992 [1], the fiber optic researchers have been engaged on Research and Development (R & D) with this type of fiber.…”
Section: Introductionmentioning
confidence: 99%
“…3 They produce lower optical transmission losses compared to standard silica optical fibers. 4 PCFs are more flexible than normal optical fibers, because it is possible to manage their properties, leading to a freedom of design.…”
Section: Introductionmentioning
confidence: 99%